2020
DOI: 10.1103/physreva.102.033105
|View full text |Cite
|
Sign up to set email alerts
|

Crystal-momentum-resolved contributions to multiple plateaus of high-order harmonic generation from band-gap materials

Abstract: We study the crystal-momentum-resolved contributions to the high-order harmonic generation (HHG) in band-gap materials, and identify the relevant initial crystal momenta for the first and higher plateaus of the HHG spectra. We do so by using a time-dependent density-functional theory model of one-dimensional linear chains. We introduce a self-consistent periodic treatment for the infinitely extended limit of the linear chain model, which provides a convenient way to simulate and discuss the HHG from a perfect … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…While much of the microscopic HHG dynamics can be understood in terms of a two-band picture [14,16,17,21,[32][33][34] involving a filled valence band and a single conduction band, a number of works have highlighted the role of multiple bands [19,[35][36][37][38][39]. In particular, it has been experimentally demonstrated that multiple bands were responsible for nonintuitive harmonic waveforms in bulk GaSe [40], the emergence of multiple plateaus in rare-gas solids [41], and yield enhancement of different harmonic regions in MgO [42].…”
Section: Introductionmentioning
confidence: 99%
“…While much of the microscopic HHG dynamics can be understood in terms of a two-band picture [14,16,17,21,[32][33][34] involving a filled valence band and a single conduction band, a number of works have highlighted the role of multiple bands [19,[35][36][37][38][39]. In particular, it has been experimentally demonstrated that multiple bands were responsible for nonintuitive harmonic waveforms in bulk GaSe [40], the emergence of multiple plateaus in rare-gas solids [41], and yield enhancement of different harmonic regions in MgO [42].…”
Section: Introductionmentioning
confidence: 99%
“…where J tot (t) is the total current in the system and W (t) is a window function of the laser-pulse-envelope shape for improving the signal-to-noise ratio. Details of the methods and parameters used as well as the periodic treatment for the limit N →∞ can be found in [19]. The laser pulse with frequency ω 0 is linearly polarized along the chain and described in dipole approximation by the vector potential A(t) = A 0 sin 2 (ω 0 t/[2n cyc ]) sin(ω 0 t) for 0 ≤ t ≤ 2πn cyc /ω 0 and A(t) = 0 otherwise.…”
mentioning
confidence: 99%
“…HHG in a condensed-matter environment shares similarities with its well-known counterpart in atoms and molecules, but also differences and richer physics due to the larger structural complexity and variability [9][10][11]. For example, the solidstate HHG cutoff was found to scale quasi-linearly with the driving field strength rather than quadratically as in atoms and molecules [1,[12][13][14]; under suitable conditions, solidstate HHG spectra exhibit multiple plateaus due to the multiple conduction bands [9,[15][16][17]. The physical mechanism underlying HHG from solids, although still being lively discussed from different perspectives [18][19][20][21][22][23][24][25], is typically described within a band picture in terms of intra-and interband processes [2,3,18] acknowledging the delocalized nature of the participating electrons.…”
Section: Introductionmentioning
confidence: 93%